Perkembangan dan peranan Persatuan Agama Buddha Amitabha Malaysia, 1993–2014 / Poey Tiang Peow - Poey , Tiang Peow (2017)
This thesis is a study on the development and role of the Amitabha Buddhist Society Malaysia (PABAM) which is located in Malaysia. The survey on the influence of the administration and management of various activities carried out by PABAM which are comprised of education, culture, welfare, and cultivation serves as the focus of this study. This analysis aims to look at the developmental trends and role of PABAM in promoting Buddhist education in Malaysia. This thesis also discusses the society’s goal towards achieving the Model of Chin Kung’s Four Holy Aims which comprise of (1) to restore Buddhism through traditional Buddhism education, (2) to encourage and develop the use of Classical Chinese language widely, (3) to expand the concept and the spirit of family tiesset out in the cultural tradition of the Chinese, and (4) to promote multi-religious and cultural education. This could transform and resolve global conflicts and maintain global security. The objective of this thesis is aimed at reviewing the extent of the development and role of PABAM in Malaysia and the main reasons of PABAM’s application of the model of Chin Kung’s Four Holy Aims to particularly benefit the believers and the local community. The research method of this thesis used both qualitative and quantitative methods. Qualitative methods include library research methods, observation and interview sessions; whilst quantitative methods were carried out through questionnaire surveys among the devotees of PABAM. This thesis uses the new Structural Functionalism Theory, the AGIL model which consists of four main factors, namely A: Adaptation, G: Goal Attainment, I: Integration, and L: Latency. The results of this study reflected PABAM’s information on how to implement and apply the Chin Kung model in the process of development and role of Buddhism in Malaysia and the main reasons of PABAM in applying the model. One of the major activities that marked the focus of PABAM in serving humanity through religion is its establishment of Dizigui School in the Philippines for the less fortunate and striving towards a policy of free education in the institution. The establishment of the institution shows the concern of PABAM that has transcended geographical boundaries. The researcher is of the view that with PABAM’s extended relations with the international community, it may be able to contribute in efforts of facing human crisis and global issues along with forces of international organizations such as the United Nations Human Rights Council. Through the international exposure, it is believed that it can further contributed to PABAM’s identity as a much more recognized religious organization among the Chinese community in Malaysia.